Penyuluhan Program Kesehatan Hutan Rakyat di Desa Tanjung Kerta Kecamatan Kedondong Kabupaten Pesawaran - Safe'i, Rahmat; Tsani, Machya Kartika (Jurnal Pengabdian Kepada Masyarakat Sakai Sambayan, 2017)
Abstract — The community forest managed by the community as tools and materials to increase revenues private forest owners sustainably. This will be achieved if the community forests have a prime forest health condition. Understanding of private forest farmers Tanjung Kerta Kedondong District Subdistrict Pesawara about the importance of forest health of the people is still very low. Many of the damage that can affect forest health conditions. However the farmers never do monitoring or supervision of forest health conditions in regullary. Private forest farmers plant crops follow market trends but does not perform proper management. The socialization of the importance of public attention to the health condition of the forest provides a more in-depth for private forest farmers that managed forests are able to provide optimum benefits to the community. Through community outreach already understand the importance of forest health of the people, as seen from the percentage increase participants' knowledge of the pre-test and post-test is 48.61%. Keywords — community forest, forest health